The Role of Halal Certification Bodies in Ensuring Consumer Confidence: A Multi-Site Study in Indonesia - Janah, Nadhivah Nur; Yazid, Muhammad (Al Ahkam, 2024)
This study examines how halal certification bodies in Indonesia contribute to consumer confidence using a multi-site qualitative approach This research focuses on exploring the perspectives of Muslim consumers, halal product manufacturers, and halal certification bodies in Jakarta, Surabaya, and Makassar, specifically the Indonesian Ulema Council (MUI) and the Halal Product Assurance Agency (BPJPH). Data was collected through in-depth interviews, focus group discussions, and observations. Findings highlight the crucial role of halal certification bodies in building consumer trust by verifying product compliance with Islamic law and ensuring transparency in the halal certification process.  Factors influencing the effectiveness of these bodies include their credibility, the clarity of halal standards, and the accessibility of information regarding halal certification.  The study also reveals varying consumer perceptions across the three cities, influenced by local socio-cultural contexts and access to information. The study also shows that consumer perceptions in the three cities differ based on local socio-cultural contexts and information availability. This research provides valuable insights for halal certification bodies to improve their effectiveness in ensuring consumer confidence and fostering the growth of the halal industry in Indonesia.